1984
DOI: 10.1159/000233454
|View full text |Cite
|
Sign up to set email alerts
|

Allergen- and Anti-IgE-Induced Histamine Release from Whole Blood

Abstract: The release of histamine by allergen and anti-IgE from whole blood was observed in 34 asthmatic subjects with a positive skin test to house dust. The time course of histamine release showed that the release by allergen and anti-IgE peaked after 15 min incubation. There was no significant difference in the time course of the release from whole blood between allergen and anti-IgE. Anti-IgE-induced histamine release correlated to a certain extent with the serum IgE level. Histamine release by house dust, on the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Furthermore, serum IgE and histamine levels were measured to determine whether allergic reactions occurred after the administration of polysorbate 20 in all SD rats. In addition to clinical signs, increased levels of serum IgE and histamine are representative indicators of an allergic reaction [36][37][38]. In the current study, allergic reactions were not observed in response to the administration of polysorbate 20, which indicated that polysorbate 20 is not an allergen in SD rats.…”
Section: Plos Onementioning
confidence: 38%
“…Furthermore, serum IgE and histamine levels were measured to determine whether allergic reactions occurred after the administration of polysorbate 20 in all SD rats. In addition to clinical signs, increased levels of serum IgE and histamine are representative indicators of an allergic reaction [36][37][38]. In the current study, allergic reactions were not observed in response to the administration of polysorbate 20, which indicated that polysorbate 20 is not an allergen in SD rats.…”
Section: Plos Onementioning
confidence: 38%
“…Whole blood samples were exposed to different concentrations of the HM and anti-IgE according to the method described by Tanizaki et al 25 Ten milliliters of venous blood was drawn into a plastic syringe containing 1 mL of heparin (17 IU/mL). Aliquots of 250 mL of different concentrations of HM (dose range, 10 24 to 10 mg/mL) and anti-IgE (dose range, 10 24 to 10 23 dilutions; Immunotech, Beckmann Coulter, Marseille, France) were added to the test tubes containing 500 mL of whole blood diluted 1:4 in Tris buffer (10 mmol/L Tris, 136 mmol/L NaCl, 2.7 mmol/L KCl, 0.23 mmol/L MgCl 2 , 1.8 mmol/ L CaCl 2 , and 5.5 mmol/L glucose, pH 7.3).…”
Section: Histamine Release Assaysmentioning
confidence: 99%
“…The challenge of whole blood with rBet v 1 and anti-IgE as a positive control was performed in a dose-response fashion according to the method described by Tanizaki et al [16]. Ten millilitres of venous blood was drawn into a plastic syringe containing 1 mL of heparin.…”
Section: Basophil Histamine Release Testmentioning
confidence: 99%